A Systematic Review of Homoeopathic Researches Comparing the Effectiveness of Homoeopathic Medicines in LM Potency vis-à-vis Centesimal Potency Scale. (Advancements in Homeopathic Research, 2022)
Objective: The objective of the study was to conduct a review of the existing literature on homoeopathic researches conducted to compare the effectiveness of LM potency vis-à-vis Centesimal potency. Materials and Methods: A comprehensive search from major biomedical databases including National Medical Library (PubMed), AYUSH PORTAL, EMBASE, Cochrane Library and Online IJRH (Official publication of Central Council for Research in Homoeopathy) was conducted using the search term “fifty millesimal potency “, “Q Potency” and “LM potency,” . Relevant research was categorised by study type and evaluated according to study design with their clinical outcomes. Results: In this review, 11 articles related to study on fifty millesimal potency were identified, out of which 3 qualified for assessment. Conclusion: All the studies concluded thatLM and CH potencies are equally effective in giving symptomatic relief to patients. The effect of two potency scales on duration of treatment was addressed in only two studies. However the difference in the homoeopathic aggravation observed by using the two scales remainedlargely unaddressed.
Keywords: Homoeopathic Posology; Scales of potentization; LM Potency; Centisemal Potency